The Impact of Product Quality and Mixue Packaging on Purchase Decisions Among Adolescents In Kartasura Subdistrict - Fuadah, Lia Samrotul; Sari, Dhany Efita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Mixue's popularity in Indonesia is high, especially in the area of Kartasura, where a lot of people, especially teenagers, are big fans of this Mixue. The study aims to test the impact of product quality on purchasing decisions and the influence of packaging on buying decisions among teenagers in cartoons. This research uses quantitative research methods with commercial causal designs. The sample in this study consisted of 200 consumers of Mixue in the Kartasura crust. Sampling is done with a saturated sample, and data collection is done by spreading the questionnaire. The results of this study show that F (simultaneous) and t (partial) tests show that product quality has a significant influence on purchasing decisions, packaging has a major influence over purchasing decision variables, and product quality and packaging have a significant impact on purchase decisions.